1974
DOI: 10.1111/j.1744-7348.1974.tb01492.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of spawning machines for mixing insecticides into mushroom compost

Abstract: SUMMARYInsecticides incorporated into mushroom compost, using a spawning machine, are seldom mixed uniformly enough to achieve satisfactory pest control. The mixing efficiencies of various application methods and machines were investigated by mapping the distributions of fluorescent granules and emulsions under ultraviolet light. The pattern in which granules were applied to a compost block greatly affected the distribution after mixing but even uniformly peppering the surface resulted in acceptable concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Control of the larvae resulting from a natural ingress of M halterau was attempted by incorporating diazin.on as an emulsion (30 mg a.i./kg) in the compost at spawning (Hussey, 1961). A spray boom was used to direct the spra} into the compost spinner ' (Wyatt and Gurney, 1974). Eleven applications c: Pynosect (Figure), mainly during the spawn-running period, were also made in ai: effort to control the ingress of M. halterata adults.…”
Section: Large-scale Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of the larvae resulting from a natural ingress of M halterau was attempted by incorporating diazin.on as an emulsion (30 mg a.i./kg) in the compost at spawning (Hussey, 1961). A spray boom was used to direct the spra} into the compost spinner ' (Wyatt and Gurney, 1974). Eleven applications c: Pynosect (Figure), mainly during the spawn-running period, were also made in ai: effort to control the ingress of M. halterata adults.…”
Section: Large-scale Testmentioning
confidence: 99%
“…The work of Wyatt and Gurney (1974) on insecticide incorporation in compost showed that up to half the compost may be undertreated owing to the inefficiency of spawning machines and the method of chemical application. Poor mixing of the diazinon and the compost in Crop B probably accounted for the number of flies caught/week being reduced by only 60 per cent compared with the untreated Crop A.…”
Section: Large-scale Testmentioning
confidence: 99%
“…However, 30%--50% of compost may be left undertreated due to inefficiency of mixing machines (Wyatt & Gurney, 1974). The generation time of cecids, compared to most mushroom pests, is very short and their population growth is exponential.…”
Section: Practical Pest Controlmentioning
confidence: 99%
“…In commercial practice, diazinon and 3' HCH are used at much higher concentrations than in the present study. However, 30%--50% of compost may be left undertreated due to inefficiency of mixing machines (Wyatt & Gurney, 1974). There are, therefore, large pockets of compost in which larvae can breed but in which they may be subjected to sublethal doses.…”
Section: Practical Pest Controlmentioning
confidence: 99%